Influência da composição secundária no potencial alelopático de Eucalyptus grandis, Mentha spicata, Plantago major e Canavalia ensiformis - Gonçalves, Deisy Brasil (2022)
The growing awareness of environmental and public health problems linked to the excessive use of agrochemicals has stimulated interest in the search for bioherbicides. In view of this, alleopathy has shown to be promising because many plants are rich in biologically active compounds that can be exploited for the production of bioherbicides. In this sense, the objective of this study was to evaluate the allelopathic effect of different concentrations (0; 1; 2.5; 5 and 10%) of aqueous and hydroalcoholic extracts of eucalyptus (Eucalyptus grandis), mint (Mentha spicata), tansage (Plantago major) and jack bean (Canavalia ensiformis) on germination and initial growth of lettuce (Lactuca sativa) and wheat (Triticum sp.) plants, as well as analyzing the presence of secondary metabolites in methanolic extracts of the species. To obtain the extracts, 20 g of previously dehydrated and crushed plant was homogenized in 100 mL of solvent, for germination and growth analysis, 25 seeds of each recipient species were placed in a gerbox with diluted aqueous and hydroalcoholic extracts (0; 1; 2.5; 5 and 10%). The experimental design was completely randomized, with three replications per treatment, with analysis of germination percentage, germination speed index (GSI), radicle and shoot length. For the phytochemical analysis, the extracts were purified and evaluated qualitatively and quantitatively using a gas detector chromatograph based on the retention time in the column. The use of both aqueous and hydroalcoholic extracts of the species tested on lettuce and wheat showed a reduction in the analyzed variables and even total inhibition of germination at the highest concentrations used. The negative allelopathic effect was greater in lettuce and with the use of eucalyptus extract compared to the other donor species. In the analysis of the eucalyptus extract, 24 compounds were detected, the most representative of which were digitoxin (14.38%), hydrocortisone acetate (12.79%) and phloroglucinic acid (11.95%), while for the mint, 17 compounds were found, being the most representative of loxanol 95 (26.23%), retinal (19.41%) and creosol (15.21%). For the tansagem species, 14 compounds were identified, the most representative being hydrocortisone acetate (53.73%), retinal (18.04%) and cortisone (5.47%). The jack bean species had 12 compounds, the most prevalent being oleic acid (60.44%), palmitic acid (11.93%) and digitoxin (7.04%). This study revealed relevant bioactive compounds, which include glycoside agents, corticosteroids, phenolic compounds, among others, indicating that the four analyzed species are sources of bioactive compounds. The presence of these molecules is related to the demonstrated allelopathic potential, and thus, it is recommended that further studies be carried out for the isolation of compounds and toxicological studies.